Pazemes Japāna: organizētās noziedzības metamorfoze no Edo perioda līdz mūsdienām - Tarnavskaya, Anna (Latvijas Universitāte, 2019)
Bakalaura darbs “Pazemes Japāna: organizētās noziedzības metamorfoze no Edo perioda līdz mūsdienām“ ir veltīts organizēto noziedzīgo grupu attīstībai Japānā, pazīstamas kā jakudza. Šī darba mērķis ir izpētīt jakudzu kā Japānas kultūras daļu, izprast izcelsmes cēloni un izsekot, kā šīs noziedzīgās grupas ir mainījušās un veidojušās vēstures gaitā. Darba autors izsekos organizēto noziedzīgo grupu attīstībai Japānā, sākot no Edo perioda līdz mūsdienām, sapratīs, kādi cilvēki pievienojas jakudzas grupām un uzzinās par bandām no iekšpuses. Darbs tika sadalīts 4 daļās, kur katra daļa aptver konkrētu laika periodu: Edo periodu (1603–1868), Meidži periodu (1868–1912), Šōvas periodu (1926-1989) un Heisei periodu (1989–2019). Bakalaura darba apjoms: 60 lappuses.

Bachelor thesis “Underground Japan: metamorphosis of the organized crimes from the Edo period until present times” is dedicated to the development of organized crime groups in Japan, known as yakuza. The aim of this work is to study yakuza as a part of Japanese culture, to understand the cause of origin and to track how these criminal groups have changed and evolved over the course of history. The author will track the development of organized crime groups in Japan, starting from the Edo period to the present day, will understand what kind of people are joining yakuza groups and will learn about gangs from inside. The work was divided into 4 parts, each part covering a specific time period: the Edo period (1603–1868), the Meiji period (1868–1912), the Shōwa period (1926-1989) and the Heisei period (1989–2019). The research paper consists of 60 pages.
Underground Japan: Metamorphosis of the Organized Crimes from the Edo Period until Present Times
Keywords: Āzijas studijas; jakudza; organizēta noziedzība; Japāna; vēsture